Influence of the elevation of the left ventricular diastolic pressure on the values of the first temporal derivative of the ventricular pressure (dP/dt) - Okoshi, Katashi [UNESP]; Fioretto, José Roberto [UNESP]; Bonatto, Rossano César [UNESP]; Tornero, Maria Teresinha Trovarelli [UNESP]; Tucci, Paulo José [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 1999)
PURPOSE: To assess the effects of the elevation of the left ventricular end-diastolic pressure (LVEDP) on the value of the 1st temporal derivative of the ventricular pressure (dP/dt). METHODS: Nineteen anesthetized dogs were studied. The dogs were mechanically ventilated and underwent thoracotomy with parasympathetic nervous system block. The LVEDP was controlled with the use of a perfusion circuit connected to the left atrium and adjusted to the height of a reservoir. The elevation of the LVEDP was achieved by a sudden increase in the height of a reservoir filled with blood. Continuous recordings of the electrocardiogram, the aortic and ventricular pressures and the dP/dt were performed. RESULTS: Elevation of the LVEDP did not result in any variation of the heart rate (167±16.0bpm, before the procedure; 167±15.5bpm, after the procedure). All the other variables assessed, including systolic blood pressure (128±18.3mmHg and 150±21.5mmHg), diastolic blood pressure (98±16.9mmHg and 115±19.8mmHg), LVEDP (5.5±2.49 and 9.3±3.60mmHg), and dP/dt (4,855 ± 1,082 mmHg/s and 5,149±1,242mmHg/s) showed significant increases following the expansion of the ventricular cavity. Although the elevation of the dP/dt was statistically significant, 6 dogs curiously showed a decrease in the values of dP/dt. CONCLUSION: Sudden elevation of the LVEDP resulted in increased values of dP/dt; however, in some dogs, this response was not uniform.
Keywords: Frank-Starling mechanism; dP/dt; ventricular function